Penegakan Hukum Terhadap Tindak Pidana Pencemaran Nama Baik Melalui Media Sosial Di Wilayah Polda Riau”. - manihuruk, trinovitasari (Faculty of Law Universitas Lancang Kuning, 2023)
The increasing criminal acts of defamation in Riau Province need serious attention. To anticipate this criminal act optimal law enforcement is carried out. How is law enforcement against criminal acts of defamation through social media by the Riau Police Sub-Directorate V (Cyber)? What are the obstacles and efforts that can be made by the Riau Police in dealing with criminal acts of defamation? The research method used is sociological legal research. Law enforcement carried out by the Riau Police is Repressive and Preventive. Repressively carried out starting from receiving reports from the public, carrying out investigations, carrying out investigations and filing of cases and also a non-penal approach, namely providing opportunities for perpetrators and victims to resolve problems outside the court. Prevention is done by outreach to the community. The obstacles are lack of personnel or human resources, lack of facilities and infrastructure and the condition of people who are not aware of the law. Efforts are being made to add personnel or Human Resources who are experts and experienced in their fields, request assistance with facilities and infrastructure, add personnel and facilities and infrastructure to the National Police Headquarters and provide outreach to the public about the ITE Law.